The concept of output alerts the crew evaluator function Navigation - Наумов, О.В. (Proceedings of National Aviation University (archive), 2007)
The version of aeronautical system CNS/ATM (Communication, Navigation, Surveillance / Air Traffic Management) is reviewed.